Pengaruh Economic Value Added, Laba Akuntansi, Risiko Sistematis, dan Prediksi Kebangkrutan terhadap Return Saham Pada Perusahaan Food and Beverage yang terdaftar di BEI Periode 2015-2019 - Yohana Srikandi Lumban Raja; Kenny Ardillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of economic value added, accounting profit, systematic risk, and bankruptcy prediction on stock returns. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The number of research samples obtained were 15 companies using purposive sampling method, and the number of research data obtained was 75. The data analysis method used was panel data regression. The results of this study indicate that systematic risk has a significant negative effect on stock returns, while economic value added, accounting earnings, and bankruptcy predictions have no effect on stock returns.